Brutalist connections: what it stands for - Zein, Ruth Verde (10º Seminário Docomomo Brasil, Curitiba, 2013, 2013)
The term Brutalism has been applied to a wide range of modern architecture buildings designed in the 194575s decades. Until recently, although the term was easily employed by several laymen and scholars sources, it had been very much overlooked or disregarded by the canonical architectural historiography. In the beginning of the 21st century it is again becoming possible, for many reasons – and the distance in time is not the less important one – to reexamine Brutalism as a dispassionate research subject: the proper use of the term and the architecture it stands for. The ideas and hypothesis here displayed are being investigated and discussed inside a broad research on mid-20th century Brutalist buildings, that already includes an ample group of hundreds of examples, situated in many places all over the world. It strives to open up its perception and to acknowledges Brutalism as a world-wide phenomenon. It proposes that, although polemical, the term Brutalism may be applied as convenient device to index these buildings in order to name and qualify a specific architectural trend of mid 20th century. It also aims to re-examine those buildings “by themselves” and to reconsider them as singular knots of a network of connections, inside the wide and complex web of modern architecture cultural and professional realm of that moment. The information on some of this buildings have already been processed and the results may be browsed at the research website at www.brutalistconnections.com.
Keywords: Brutalism; Distant readings; Mid-20th century modern architecture